Growth and development of early upland cotton CNPA precoce cultivar in the hinterland of the sate of Paraíba, Brazil. - Beltrão, Napoleão Esberard de Macêdo; Nóbrega, Laudemiro Baldoíno da; Vieira, Dirceu Justiniano; Azevêdo, Demóstenes Marcos Pedrosa de; Souza, Roberto Pequeno de (Pesquisa Agropecuaria Brasileira, 2014)
Aiming to investigate the "CNPA Precoce 1" cotton (Gossypium hirsutum L.) cultivar, originated from the GH 11-9-75 North American line, under the mesological conditions of the hinterland of the state of Paraíba, Brazil, concerning the growth and development stand, an experiment was carried out during the 1986 agricultural year, and repeated in 1987 under edafic middle Vertisol soil associate conditions. In the first year, with irregular rainfall and no fertilization, the genotype showed the best leaf area (2,912.9 m2/plant), and the highest number of squares (14/plant) was obtained at 60 days after emergence. Cotton seed yield (1,377 kg/ha) did not depend on the 1.0 mx 0.2 m and (1.0 mx 0.2 m) plant configurations. In 1987, with more regular rainfalls and soil fertilization, the maximum leaf área (7.087.9 cm2/plant) was obtained at 75 days from the emergence. The highest number of bud squares (20.4) was obtained 60 days after planting. The yields of the (0.6 mx 0.2 m) (1.0 m x 0.2 m) x 0.2 m plant configurations were higher (3,620 and 3,557 kg/ha, respectively) than that one with 1.0 mx 0.2 m (2,455 kg/ha).